A Reminiscence of ”Mastermind”: Iris/Periocular Biometrics by ”In-Set” CNN Iterative Analysis - Proença, H. (2020)
Submitted by PROENÇA (hugomcp@ubi.pt) on 2020-02-06T16:02:26Z No. of bitstreams: 1 Mastermind_TIFS.pdf: 5308376 bytes, checksum: 5ccfa3434497a25683981b049d2ca485 (MD5)